Ultrastructural changes in the rabbit retina after various one-time doses of intravitreal melphalan (Ukrainian Journal of Ophthalmology, 2025)
Background: Intravitreal chemotherapy (IVC) has become a common eye-preserving treatment for retinoblastoma (RB). However, there are still unsolved issues with regard to dosage of the cytostatic agent, its ultrastructural effects on healthy retinal cells, and late complications of the therapy.Purpose: To identify and assess ultrastructural changes in the rabbit retina after various one-time doses of intravitreal melphalan.Material and Methods: Six eyes of three Chinchilla rabbits (age, 5–6 months; weight, 2.5–3 kg) underwent clinical and electron miscroscopy examination. Both eyes of animals ##1, 2 and 3 received a single dose of intravitreal melphalan of 5, 10 and 20 ?g, respectively. Intravitreal injection was performed in a standard manner. The eyes were enucleated 4 weeks after injection. After enucleation, material for histology was taken in a routine manner and examined in a PEM-100-01 electron microscope.Results: Intravitreal injection of various doses of melphalan had no general toxic effect on the animals. No retinal hemorrhage, vitreous hemorrhage, retinal tear or detachment was observed at all follow-up points, regardless of how large an intravitreal dose of melphalan was administered. No complications were observed postoperatively. Throughout a follow-up period of 4 weeks, there were no focal fundus changes in the eyes that received a single intravitreal injection of 5 ?g melphalan. In the eyes that received a single intravitreal injection of 10-?g or 20-?g melphalan, we noted a range of focal fundus changes from as mild as a few small isolated sites of slight depigmentation to as severe as pigment redistribution with the emergence of brighter and greater depigmentation regions in the retina. Ultrastructural changes corresponded to ophthalmoscopic changes. Electron microscopy revealed destructive changes in the retinal pigment epithelium (RPE), photoreceptors, and M?ller cells of the rabbit retina. The minimum structural changes in the RPE and photoreceptor cells were seen after an injection of the smallest dose (5 ?g melphalan). After a 10-?g or 20-?g one-time dose of intravitreal melphalan, we observed severe changes (such as cell swelling, hypertrophy, destruction and disintegration) in retinal cells, disorganized retinal layers with loss of typical ultrastructural features, gliosis and necrosis.Conclusion: On the basis of our findings, we can conclude that intravitreal melphalan is relatively safe when administered as a one-time 5-?g injection, and minimally toxic when administered as a one-time 10-?g injection. However, when administered as a one-time 20-?g injection, it resulted in severe changes such as gliosis and necrosis in retinal cells.
Keywords: intravitreal chemotherapy; melphalan; electron microscopy; retina; experiment